Inverse correlation of intact PTH, oxidized PTH as well as non-oxidized PTH with 25-hydroxyvitamin D3 in kidney transplant recipients - Zuo, Jiao; Hasan, Ahmed A.; Hocher, Carl-Friedrich; Kalk, Philipp; Kleuser, Burkhard; Krämer, Bernhard K.; Hocher, Berthold (Frontiers in Endocrinology, 2023)
25-hydroxyvitamin D (25(OH)D) and potentially also 1,25-dihydroxyvitamin D (1,25(OH)2D) inhibits the synthesis of parathyroid hormone (PTH) in the chief cells of the parathyroid gland. Clinical studies showing a negative correlation between (25(OH)D and PTH are in good agreement with these findings in basic science studies. However, PTH was measured in these studies with the currently clinically used 2nd or 3rd generation intact PTH (iPTH) assay systems. iPTH assays cannot distinguish between oxidized forms of PTH and non-oxidized PTH. Oxidized forms of PTH are the by far most abundant form of PTH in the circulation of patients with impaired kidney function. Oxidation of PTH causes a loss of function of PTH. Given that the clinical studies done so far were performed with an PTH assay systems that mainly detect oxidized forms of PTH, the real relationship between bioactive non-oxidized PTH and 25(OH)D as well as 1,25(OH)2D is still unknown. To address this topic, we compared for the first time the relationship between 25(OH)D as well as 1,25(OH)2D and iPTH, oxPTH as well as fully bioactive n-oxPTH in 531 stable kidney transplant recipients. There was an inverse correlation between 25(OH)D and all forms of PTH, including oxPTH (iPTH: r=-0.197, p<0.0001; oxPTH: r=-0.203, p<0.0001; n-oxPTH: r=-0.146, p=0.001). No significant correlation was observed between 1,25(OH)2D and all forms of PTH. Multiple linear regression analysis considering age, PTH (iPTH, oxPTH and n-oxPTH), serum calcium, serum phosphor, serum creatinine, fibroblast growth factor 23 (FGF23), osteoprotegerin (OPG), albumin, and sclerostin as confounding factors confirmed these findings. Subgroup analysis showed that our results are not affected by sex and age. In conclusion, all forms of PTH are inversely correlated with 25-hydroxyvitamin D (25(OH)D). This finding would be in line with an inhibition of the synthesis of all forms of PTH (bioactive n-oxPTH and oxidized forms of PTH with minor or no bioactivity) in the chief cells of the parathyroid glad.